Model Hubungan Manajemen Pembinaan dan Lingkungan Pendidikan Terhadap Karakter Kepemimpinan Kadet Unhan RI - Ansori Zaini; Damianus Manesi; Imanuel A. Tnunay; Raymundus P. Situmorang; Yosy Gustasya (Universitas Nusa Cendana, 2026)
This study aims to analyze the relationship between mentoring management and the educational environment on the leadership character of cadets in the Ship Machinery Study Program at the Indonesian National Defense University. The study employs a quantitative approach with an associative design. The study population consisted of 75 cadets, all of whom were included in the sample using total sampling. Data were collected using a Likert-scale questionnaire that had been tested for validity and reliability, and then analyzed using multiple linear regression. The results indicate that both training management and the educational environment, both partially and simultaneously, have a positive and significant effect on cadet leadership characteristics. Training management is the most dominant variable in influencing leadership. Simultaneously, the two variables contribute 46.4% to leadership character. These findings indicate that the development of cadet leadership character requires integration between structured training and a conducive educational environment. This study recommends improving the quality of training management as well as strengthening academic culture and discipline as strategic efforts to develop excellent and integrity-driven cadet leadership